The Nutritional Properties, Chemical Compositions, and Functional Characteristics of the Aerial Parts of Adonis coerulea - Dai, Lixia; Li, Bing; Yang, Xiaorong; Wang, Yu; Pan, Hu; Zhang, Jiyu; Shang, Xiaofei (Frontiers in Nutrition, 2022)
The nutrition and active compounds from plants are very important to regulate the immunity of body by improving the oxidant and inflammatory response. In this paper, we aimed to investigate the nutritional profile and the phytochemical compositions of Adonis coerulea, the functional characteristics and its possible mechanism were studied. Results showed that the aerial parts of A. coerulea (ACAP) contained the abundant of proteins (16.15 %) and the minerals (31.02.09 mg/100 g dried ACAP), the promisingly the content of essential amino acids (8.25 %) and fatty acids (13220.45 mg/100 g) also were obtained to regulate the immunity and prevent some chronic diseases. The methanol extract of ACAP played the anti-inflammatory activity via PPAR-γ mediated NF-кB pathway. Among of 18 identified compounds, linolenic acid from fatty acids and licochalcone A were active compounds by inhibiting nitric oxide (NO) production of RAW264.7 cells induced by lipopolysaccharide (LPS). The alleviation of inflammatory response results in the decrease of oxidative stress, ACAP showed the anti-oxidant activity by attenuating antioxidant enzymes, improving mitochondrial membrane potential and reactive oxygen species. These results highlight the potential of A. coerulea as a source of active ingredients in pharmaceutical industries.